Factors Affecting Adherence to Antiretroviral (ARV) Medication in HIV Positive Patients : Faktor Kepatuhan Minum Obat ARV (Antiretroviral) Pada Penderita HIV Positif - Christy Desmery; Iskandar Arfan; Ismael Saleh (Muhammadiyah Institute of Technology and Health, West Kalimantan (ITEKES Muhammadiyah Kalimantan Barat), 2024)
The adherence of HIV AIDS patients in ARV therapy is one of the important factors in the success of HIV AIDS treatment, because continuous and uninterrupted ARV will be able to suppress the progression of the virus, reduce viral resistance, improve the patient's quality of life and improve their general health. The purpose of this study is to analyze factors related to compliance with taking ARV drugs in HIV-positive patients at the Klinik Klinik Melati Hospital dr. Soedarso Pontianak. The sample is 62 respondents who have met the inclusion criteria. Research design: this study uses quantitative research, with a cross sectional design. The results of the study show that there is no relationship between education levels. employment, motivation, family support, drug side effects, health worker support with compliance with taking ARV drugs, while patient knowledge is related to compliance with taking ARV drugs. Suggestions for institutions to provide more education to increase the knowledge of HIV patients to know the importance of adherence to taking ARV drugs for the survival of ODHA. Keywords: Compliance with ARV Medication, HIV Kepatuhan pasien HIV AIDS dalam terapi ARV merupakan salah faktor yang penting dalam keberhasilan pengobatan HIV AIDS, karena ARV yang berkelanjutan tanpa terputus akan mampu menekan perkembangan virus, mengurangi resistensi virus, memperbaiki kualitas hidup pasien dan memperbaiki kesehatannya secara umum. Tujuan dari penelitian ini adalah untuk menganalisa faktor-faktor yang berhubungan dengan kepatuhan minum obat ARV pada penderita HIV positif di Poli Kilinik Melati RSUD dr. Soedarso Pontianak. Sampel sebanyak 62 Responden yang sudah memenuhu kriteria inklusi. Desain penelitian: penelitian ini menggunakan penelitian kuantitatif, dengan desain cross sectional. Hasil Penelitian menunjukan bahwa tidak ada hubungan antara tingkat pendidikan. perkerjaan, motivasi, dukungan keluarga, efek samping obat, dukungan petugas kesehatan dengan kepatuhan minum obat ARV, sedangkan pengetahuan pasien mempunyai hubungan dengan kepatuhan minum obat ARV. Saran untuk institusi agar memberikan edukasi yang lebih untuk meningkatkan pengetahuan pasien HIV agar mengetahui pentingnya kepatuhan minum obat ARV untuk kelangsungan hidup ODHA. Kata Kunci: Kepatuhan Minum Obat ARV, HIV